Réponse :
Bonjour,
Explications étape par étape
[tex]\overrightarrow{AB}=\vec{i}\\\overrightarrow{AD}=\vec{j}\\\\\overrightarrow{AO}=\dfrac{\vec{i}}{2} +\dfrac{\vec{j}}{2} \\\\\overrightarrow{OI}=\overrightarrow{OA}+\overrightarrow{AI}\\\\=-\dfrac{\vec{i}}{2} -\dfrac{\vec{j}}{2}+2\vec{i}\\\\=\dfrac{3\vec{i}}{2}-\dfrac{\vec{j}}{2}\\\\\overrightarrow{OJ}=\overrightarrow{OA}+\overrightarrow{AJ}\\\\=-\dfrac{\vec{i}}{2} -\dfrac{\vec{j}}{2}-\vec{j}\\\\=-\dfrac{\vec{i}}{2}-\dfrac{3\vec{j}}{2}\\\\[/tex]
[tex]\overrightarrow{OI}\ .\ \overrightarrow{OJ}\\\\=(\dfrac{3\vec{i}}{2} -\dfrac{\vec{j}}{2})\ .\ (-\dfrac{\vec{i}}{2} -\dfrac{3\vec{j}}{2}) \\\\=\dfrac{-3}{4} +\dfrac{3}{4} \\=0[/tex]